Digital crime Reporting FIR Management and Online Complaint System (International Journal of Scientific Research in Science and Technology, 2025)
In the digital age, traditional methods of filing First Information Reports (FIRs) and lodging complaints with law enforcement agencies often suffer from inefficiency, inaccessibility, and delays. This paper presents a comprehensive web-based solution titled Digital Crime Reporting: FIR Management and Online Complaint System, which enables citizens to report crimes and file complaints online through a secure and user-friendly interface. The proposed system leverages JSP, Servlets, and a MySQL backend to facilitate real-time FIR registration, complaint tracking, status updates, and administrative oversight. Key features include digital FIR submission with photo uploads, PDF generation, complaint status tracking (e.g., Pending, In Progress, Completed), police login for verification and response, and secure data handling. Additionally, advanced functionalities such as officer signature capture, document upload, and chat-based communication between officers are integrated to enhance inter-departmental coordination. This system aims to improve transparency, reduce bureaucratic friction, and ensure timely action in criminal justice processes. The implementation demonstrates how digital platforms can bridge the gap between law enforcement agencies and the public, fostering trust and accountability.